Hope as a Moderator of Intimate Partner Violence and Suicide Risk Behaviors Among Latinas - Edwards, Lisa M. (Violence against women, 2023)
The current study investigated the role of hope in the relationship between intimate partner violence (IPV) and suicide risk behaviors among a community sample of Latinas (N = 180). Moderation analyses revealed significant interaction effects demonstrating that both aspects of hope—agency and pathways—were associated with suicide risk behaviors at high levels of IPV. Results suggest hope may be helpful when IPV is at low levels, but it may exacerbate suicide risk when high levels of IPV are experienced among Latinas. Future directions and implications are discussed, including the importance of understanding the unique cultural context in which Latina survivors exist.